The impact of macroeconomic factors on real estate prices : evidence from Montenegro - Radonjić, Milena (Array, 2019)
The real estate market, as one of the most volatile economic sectors, is a key research topic for many authors. Regardless the significance of this topic, no previous research has been conducted to evaluate the factors which influence the price of real estate in Montenegro. Therefore, the objective of this study is to clarify whether the trend in real estate prices in Montenegro can be explained by macroeconomic fundamentals such as GDP, the inflation rate, interest rates on mortgages, take-up of mortgages, the unemployment rate, the average net salary, the current account deficit and constructing activity and to determine which of them is the most important in explaining the price trend for this market. The applied methodology is based on the model averaging technique, which has not been used in previous research on this topic; it enables the research to focus on the relevant results despite the short time series and the large number of independent variables. The results obtained point to the fact that price trends in real estate are best described by and most closely align to GDP. Apart from GDP, net salary, the unemployment rate as well as the take-up of mortgages and their interest rates are shown to be significant as variables, which determine price trends within the real estate market.